SMC translocation is unaffected by an excess of nucleoid associated proteins in vivo - Zhongqing Ren; Lindsey E. Way; Xindan Wang (Scientific Reports)
Abstract Genome organization is important for DNA replication, gene expression, and chromosome segregation. In bacteria, two large families of proteins, nucleoid-associated proteins (NAPs) and SMC complexes, play important roles in organizing the genome. NAPs are highly abundant DNA-binding proteins that can bend, wrap, bridge, and compact DNA, while SMC complexes load onto the chromosome, translocate on the DNA, and extrude DNA loops. Although SMC complexes are capable of traversing the entire chromosome bound by various NAPs in vivo, it is unclear whether SMC translocation is influenced by NAPs. In this study, using Bacillus subtilis as a model system, we expressed a collection of representative bacterial and archaeal DNA-binding proteins that introduce distinct DNA structures and potentially pose different challenges for SMC movement. By fluorescence microscopy and chromatin immunoprecipitation, we observed that these proteins bound to the genome in characteristic manners. Using genome-wide chromosome conformation capture (Hi-C) assays, we found that the SMC complex traversed these DNA-binding proteins without slowing down. Our findings revealed that the DNA-loop-extruding activity of the SMC complex is unaffected by exogenously expressed DNA-binding proteins, which highlights the robustness of SMC motors on the busy chromatin.